Restoration of macroinvertebrates, fish, and habitats in streams following mining subsidence: replicated analysis across 18 mitigation sites. Issue 5 (13th February 2017) - Nuttle, Tim; Logan, Marisa N.; Parise, David J.; Foltz, David A.; Silvis, Joshua M.; Haibach, Mark R.
Abstract: Human activities have led to declines in stream functioning and stream restoration seeks to reverse this trend. Longwall coal mining, an underground full‐extraction method, can cause surface subsidence, affecting streams by creating a series of deep pools that trap sediment, reduce habitat diversity, and impair macroinvertebrate and fish communities. Mining effects on streams must be mitigated to maintain the functions, values, and foreseeable uses of streams. Gate cutting is a procedure that alleviates pooling by reestablishing the stream grade, accompanied by procedures that stabilize the channel, restore substrates, and enhance in‐stream and riparian habitats. We evaluated effectiveness of gate cuts at restoring streams affected by subsidence pooling at 18 independent restoration sites over two mines in southwestern Pennsylvania, U.S.A. At each site, sampling stations were established to monitor effects of mining subsidence and its restoration on macroinvertebrates, fish communities, and habitats. We tested for effects of sequential interventions (subsidence and restoration) on biological and habitat variables in a replicated before–after design, controlling for potentially confounding temporal effects (sample month and antecedent effective precipitation). All biological indices and substrate‐related habitat indices declined following subsidence but improved following restoration. Macroinvertebrate indicex and taxa richness, substrates, and riparian vegetation continued to improve with time following restoration. Whereas other studies have concluded that biological communities may take many years to respond to restoration, these results indicate that where macroinvertebrate and fish communities are altered by subsidence pooling, they can be effectively restored using gate cuts to pre‐mining levels within relatively short time periods.